2006
DOI: 10.1207/s15328015tlm1803_5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Internal Medicine Residents as Exercise Role Models and Associations With Self-Reported Counseling Behavior, Confidence, and Perceived Success

Abstract: Most internal medicine resident physicians may not be adequate role models for promoting exercise adherence. Confidence in the knowledge of current guidelines, personal physical activity enjoyment, and perceived success and self-efficacy in engaging in regular physical activity may be useful targets for enhancing resident physician physical activity counseling for their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 21 publications
4
57
2
1
Order By: Relevance
“…11 Literature review confirmed low counseling rates of patients at risk for CVD in our program 6 and in other residency programs [12][13][14] and documented studies on reported barriers to physician counseling. [15][16][17] We then conducted a targeted needs assessment defined in step two of Kern's six-step approach as "assessing the needs of one's targeted group of learners and their medical institution/ learning environment, which may be different from the needs of learners and medical institutions in general." At study initiation in 2006, faculty preceptors perceived nutrition and exercise counseling rates remained low in resident clinics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Literature review confirmed low counseling rates of patients at risk for CVD in our program 6 and in other residency programs [12][13][14] and documented studies on reported barriers to physician counseling. [15][16][17] We then conducted a targeted needs assessment defined in step two of Kern's six-step approach as "assessing the needs of one's targeted group of learners and their medical institution/ learning environment, which may be different from the needs of learners and medical institutions in general." At study initiation in 2006, faculty preceptors perceived nutrition and exercise counseling rates remained low in resident clinics.…”
Section: Methodsmentioning
confidence: 99%
“…To assess professional attitudes toward counseling, we developed open and closed ended questions regarding potential barriers based on published barriers to counseling. [12][13][14][15][16][17] We then developed questions on resident practices in physical activity and nutrition counseling. The self-administered KAP survey used multiple choice questions for the knowledge and practices portions and 5-point Likert scale questions for the attitudes portion.…”
Section: Kap Questionnairementioning
confidence: 99%
“…16,35,36 This sample of oncology nurses did not exercise at the level recommended by the CDC. 30 Personal experience with exercise was not related to the exercise benefits beliefs nor the exercise barriers beliefs of nurses, suggesting that personal experience with exercise may not be an important contextual factor that affects nurses' beliefs in exercise as a treatment for women with breast cancer experiencing CRF.…”
Section: Discussionmentioning
confidence: 99%
“…1,15,16 According to the ONS, about 10% of patients with breast cancer received recommendation to exercise in order to reduce their fatigue.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation